2003
DOI: 10.1007/s10286-003-1111-5
|View full text |Cite
|
Sign up to set email alerts
|

Sequelae of endoscopic sympathetic block

Abstract: Endoscopic sympathetic block as a treatment for primary hyperhidrosis is associated with certain sequelae. The reported occurrence of side effects still varies in the literature. As the majority of patients describe sequelae after sympathetic surgery, the frequency and importance of these persisting changes are still underestimated. Patient's informed consent should include and define side effects like gustatory sweating, olfactory sweating and bradycardia as likely, and compensatory sweating as obligatory.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2005
2005
2008
2008

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…25,69 Because sympathetic cardiac accelerator fibers exit the spinal cord from segments T1 to T4, ETS is believed to simulate a mild physiological β-adrenergic blockade. 70 This is because the heart rate at rest and during maximal exercise is lower 6 weeks postoperatively, 69,71 but exercise capacity is not affected. As for pulmonary sympathetic denervation, no significant detrimental effect on pulmonary function has been shown in children and adults.…”
Section: Sympathetic Denervationmentioning
confidence: 99%
“…25,69 Because sympathetic cardiac accelerator fibers exit the spinal cord from segments T1 to T4, ETS is believed to simulate a mild physiological β-adrenergic blockade. 70 This is because the heart rate at rest and during maximal exercise is lower 6 weeks postoperatively, 69,71 but exercise capacity is not affected. As for pulmonary sympathetic denervation, no significant detrimental effect on pulmonary function has been shown in children and adults.…”
Section: Sympathetic Denervationmentioning
confidence: 99%
“…27 Other authors reported CS ranging between 44% and 86% after ESB at different levels ranging between T1 and T4. 28 In another study, clipping of the upper part of the T4 ganglion resulted in 87.5% of patients exhibiting CS. 29 According to Reisfeld et al, 3 these numbers are of minor interest because the percentage of patients with severe CS is of major importance.…”
Section: Commentmentioning
confidence: 95%
“…The exact mechanism for this is still unknown. It may be a consequence of particular surgical methods [4,8,9,24]. Some surgeons report a lesser incidence of compensatory sweating after an extensive sympathectomy [11] and others after a limited surgical procedure [13].…”
Section: Discussionmentioning
confidence: 98%